2018
DOI: 10.1016/j.chemosphere.2018.06.129
|View full text |Cite
|
Sign up to set email alerts
|

Impact of interaction between Limnoperna fortunei and Roundup Max® on freshwater phytoplankton: An in situ approach in Salto Grande reservoir (Argentina)

Abstract: The joint impact of the glyphosate-based commercial formulation Roundup Max and the invasive mussel Limnoperna fortunei on phytoplankton and water quality was assessed in Salto Grande reservoir, a scenario were both stressors coexist. We performed an in situ mesocosm approach, through a 7-day experiment using 400-L enclosures. The following treatments were applied by triplicate: addition of 250 mussels (M); addition of 5 mg L of active ingredient (a.i.) in Roundup Max (R); addition of 250 mussels and 5 mg L of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
6
0
1
Order By: Relevance
“…These organisms were frequently used in early studies on photosynthesis [ 72 ] and are distributed in both freshwater and marine environments [ 73 , 74 ]. In the present study, Chlamydomonadales X , consisting mainly of Spermatozopsis and Chlamydomonas , were largely distributed in freshwater environments, although Chlamydomonas could also be found in seawater environments [ 75 , 76 , 77 ]. The algae of Sphaeropleales X are common planktonic freshwater algae [ 78 ], and, in the current study, their members were mainly detected in samples taken from freshwater environments.…”
Section: Discussionmentioning
confidence: 68%
“…These organisms were frequently used in early studies on photosynthesis [ 72 ] and are distributed in both freshwater and marine environments [ 73 , 74 ]. In the present study, Chlamydomonadales X , consisting mainly of Spermatozopsis and Chlamydomonas , were largely distributed in freshwater environments, although Chlamydomonas could also be found in seawater environments [ 75 , 76 , 77 ]. The algae of Sphaeropleales X are common planktonic freshwater algae [ 78 ], and, in the current study, their members were mainly detected in samples taken from freshwater environments.…”
Section: Discussionmentioning
confidence: 68%
“…In complement, Neury‐Ormanni et al (2020) suggested that a poor microalgae quality subsequent to diuron exposure (e.g., decreased content in essential fatty acids, see below) could trigger invertebrates to graze higher amounts of contaminated microalgae, to compensate for the decrease in nutrient supply (also see section Dissipation and mitigation of contaminants ). The impacts of glyphosate on phytoplankton were also shown to be altered in the presence of golden mussels ( Limnoperna fortunei ), the addition of which modified nutrient content in the water column and selected for phytoplankton species (De Stefano et al, 2018; Gattás et al, 2018). Such results contrast with those of Iummato et al (2017), who found no differences in periphyton exposed or not to glyphosate in the presence of L. fortunei , suggesting that the mussels attenuated the effects of glyphosate by contributing to its dissipation, and of López‐Doval et al (2010), who did not observe any significant interactions between diuron, biofilms, and grazers (freshwater snail Physella acuta ).…”
Section: Resultsmentioning
confidence: 99%
“…Eutrophication, accompanied by continued economic development, especially in densely populated areas of the world, constantly threatens the service functions of freshwater systems . High concentrations of herbicides may affect the growth of microalgae and cyanobacteria by altering their metabolic profile, , and they may even contribute to the formation of harmful cyanobacterial blooms (cyanoHABs). , Algae are sensitive to herbicides, and there is also great variability in species sensitivity. Studies show that the low sensitivity of cyanobacteria, a typical prokaryotic phytoplankton, to glyphosate-based herbicides and its ability to utilize phosphonates might be the key for its predominance. , Under the multiple challenges of climate warming and human activities, toxic cyanobacterial blooms tend to occur more frequently and for longer periods of time, further threatening future human health and ecosystem services. Therefore, it is necessary to fill the knowledge gaps of the results of this interaction to support future lake management decisions or climate mitigation interventions to protect and restore freshwater ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…7 High concentrations of herbicides may affect the growth of microalgae and cyanobacteria by altering their metabolic profile, 8,9 and they may even contribute to the formation of harmful cyanobacterial blooms (cyanoHABs). 10,11 Algae are sensitive to herbicides, 12 and there is also great variability in species sensitivity. Studies show that the low sensitivity of cyanobacteria, a typical prokaryotic phytoplankton, to glyphosate-based herbicides and its ability to utilize phosphonates might be the key for its predominance.…”
Section: ■ Introductionmentioning
confidence: 99%